Rapor Pendidikan Indonesia: Quo Vadis Kualitas Pendidikan Indonesia? - Dwi Shintia; Masduki Asbari; Fadhila Khairunisa; Nurul Azizah (AGUSPATI RESEARCH INSTITUTA, 2023)
The aim of this study is to determine how to improve the quality of education in Indonesia by providing integrated and data-based information to education units and local governments for reflection and improvement. In this study report, a descriptive qualitative method was used by taking notes because the data source was obtained by listening to the oral narrative from the Indonesian Ministry of Education and Culture's Youtube channel entitled